Combination or sequential teriparatide for osteoporosis treatment in denosumab-users: real-world bone mineral density outcomes - Shejil KUMAR; Courtney STREETER; Michelle M. MCDONALD; Roderick J. CLIFTON- BLIGH; Matti L. GILD; Christian M. GIRGIS (Bone Reports)
The optimal osteoanabolic strategy in denosumab (Dmab)-users remains uncertain. In treatment-naïve patients, Dmab/teriparatide (TPTD) combinations result in dramatic bone mineral density (BMD) gains at the spine and hip. However, BMD outcomes with combination Dmab/TPTD have not been investigated in patients on established Dmab.We retrospectively reviewed patients with osteoporosis at two Sydney centers between 2013 and 2023. Eligible patients were managed with Dmab immediately before ≥12-months TPTD. Patients were grouped according to whether TPTD was added to ongoing Dmab (combination) or Dmab was withheld during TPTD (sequence). BMD outcomes were assessed during TPTD.The total cohort (N = 23; 11 = combination, 12 = sequence) had mean age 77 ± 7 years and were predominantly female (87 %). Overall, prior vertebral (52 %) and non-vertebral fractures (2.4 ± 1.5) were prevalent and pre-TPTD BMD T-scores (SD) low at lumbar spine (−2.4 ± 1.2) and total hip (−2.2 ± 0.6). Median Dmab exposure was 5-doses (IQR 3–11), median overall antiresorptive exposure was 6-years (IQR 4–11) and majority (>90 %) received 18-months TPTD. Groups were similar in age, sex, Dmab and overall antiresorptive exposure, fracture prevalence, DXA interval and pre-TPTD BMD values. Combination Dmab/TPTD was associated with significant lumbar spine BMD gains (+0.080 g/cm2 ± 0.059 g/cm2, p = 0.004; +9.8 %). No significant BMD change occurred during sequential Dmab/TPTD (+0.026 g/cm2 ± 0.049 g/cm2, p = 0.107; +3.5 %). Combination Dmab/TPTD resulted in greater lumbar spine BMD gains (p = 0.039). Hip and femoral neck BMD remained stable in both groups.In this retrospective study, significant lumbar spine BMD gains occurred during combined Dmab/TPTD in patients on established Dmab. These results warrant prospective controlled studies to further inform optimal osteoanabolic strategies in Dmab-users.